6G Use Cases and Scenarios: A Comparison Analysis Between ITU and Other Initiatives - Alessandro Vizzarri; Franco Mazzenga (Future Internet)
In the next decade, the amount of network traffic is estimated to reach Zettabytes. The future International Mobile Telecommunications-2030 (IMT-2030) standard of mobile networks, known as 6G, introduces an important paradigm shift in the context of wireless communication systems thanks to capabilities such as low latency and high data rates. Official documents on 6G standardization have been released by the International Telecommunication Union (ITU). However, other visions and use cases of 6G have been proposed by industrial stakeholders and research institutions, thus generating a multitude of use cases and usage scenarios that are only apparently different from each other. This paper would contribute to providing a holistic vision of the 6G-enabled use cases and potentially impacted vertical market sectors. The differences and similarities between what has been proposed by ITU and other initiatives are identified through a comparison based on the technological characterization of use cases and of the considered vertical market sectors. The main findings presented in this paper demonstrate that many of the use cases proposed by ITU and by the other initiatives are almost identical in many cases.